The effect of service quality on customer satisfaction and customer loyalty among Bank Mandiri customers in Indonesia - Muhammad Sayoga; Indarini; Dudi Anandya (Southeast Asian Journal of Service Management, 2025)
This study aims to analyze the effect of five dimensions of service quality, namely reliability, responsiveness, visibility, employee commitment, and access to service, on customer satisfaction, as well as the effect of customer satisfaction on customer loyalty among Bank Mandiri customers in Indonesia. This study uses a descriptive quantitative research method. Data collection in this study used questionnaire respondents' data distributed using the Google Form platform. Data processing methods used SPSS 24 and AMOS 23 software. The results show that of the six hypotheses tested, five were supported: reliability has a positive effect on customer satisfaction, responsiveness has a positive effect on customer satisfaction, visibility has a positive effect on customer satisfaction, employee commitment has a positive effect on customer satisfaction, and customer satisfaction has a positive effect on customer loyalty. One hypothesis was not supported: access to service does not have a positive effect on customer satisfaction. These findings provide insights for Bank Mandiri to improve the dimensions of service quality that are most influential in creating customer satisfaction and customer loyalty.